A systematic review of the matrix training literature. (19th March 2021) - Kemmerer, Ashley R.; Vladescu, Jason C.; Carrow, Jacqueline N.; Sidener, Tina M.; Deshais, Meghan A.
Abstract: The rapid acquisition and generality of skills are important considerations when developing teaching techniques in various educational settings. Acquiring skills without direct teaching reduces instructional time, improves efficiency, and saves money. These desirable outcomes can be achieved through generative instruction such as matrix training. Numerous studies have evaluated the effectiveness of the matrix training strategy, but there are several procedural variations in developing a matrix training procedure. The current literature requires a comprehensive review to determine what strategies are effective when arranging a matrix training procedure and directions for future research. The purpose of this literature review was to identify all of the studies that have used a matrix training approach to teach a skill. A total of 35 articles (containing 40 experiments) were identified and included in this review. The articles were coded according to several parameters including participant characteristics, dependent and independent variables, outcomes, maintenance, and social validity. The results of this review indicate the variation in implementation strategies employed during matrix training. Limitations of the current literature as well as directions for future research are discussed.